2018
DOI: 10.1111/ejn.13959
|View full text |Cite
|
Sign up to set email alerts
|

Neuroplasticity in stroke recovery. The role of microglia in engaging and modifying synapses and networks

Abstract: Neuroplasticity after ischaemic injury involves both spontaneous rewiring of neural networks and circuits as well as functional responses in neurogenic niches. These events involve complex interactions with activated microglia, which evolve in a dynamic manner over time. Although the exact mechanisms underlying these interactions remain poorly understood, increasing experimental evidence suggests a determining role of pro- and anti-inflammatory microglial activation profiles in shaping both synaptogenesis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 155 publications
(205 reference statements)
1
69
0
Order By: Relevance
“…At the same time myelin-associated growth inhibitors are released through exosomes from oligodendrocytes [ 195 ]. Therefore, active production of exosomes in the injuries areas of CNS may have a strong effect on CNS neuroplasticity, including collateral sprouting and unmasking of latent synapses [ 196 , 197 ].…”
Section: Evs In Axon Regenerationmentioning
confidence: 99%
“…At the same time myelin-associated growth inhibitors are released through exosomes from oligodendrocytes [ 195 ]. Therefore, active production of exosomes in the injuries areas of CNS may have a strong effect on CNS neuroplasticity, including collateral sprouting and unmasking of latent synapses [ 196 , 197 ].…”
Section: Evs In Axon Regenerationmentioning
confidence: 99%
“…Microglia also contribute to the maintenance of homeostasis within the CNS, including promoting neuronal survival and mediating synaptic plasticity [24,25]. These roles involve the secretion of trophic factors, e.g., brain-derived neurotrophic factor (BDNF) [26,27], insulin-like growth factor-1 (IGF-1) [28] and pruning of neuronal synapses, which involves complement factor C1q [29][30][31]. Microglia also remodel the extracellular matrix through the secretion of several proteolytic enzymes, such as matrix metalloproteases (MMPs) and tissue-type plasminogen activator (tPA) [28].…”
Section: Microglial Morphology "Activation" States and Functions In mentioning
confidence: 99%
“…Previous experimental studies have shown a neuroprotective effect of acute MMP-9 inhibition in stroke (Asahi et al, 2000) whereas MMP-9 inhibition in the early recovery phase exacerbated stroke-induced brain damage (Zhao et al, 2006). Several other pathophysiological processes have shown a similar unexpected biphasic function after stroke (Ma et al, 2017;Sandvig et al, 2018). Only long-term observations of cohorts with acceptable survival rates allow to assess the full picture of postischemic vascular inflammation, its resolution and tissue repair.…”
Section: Introductionmentioning
confidence: 99%